Effects of traditional concurrent training and multicomponent training composed by strength training and dance classes on functional and cognitive capacity of older adults: a study protocol - Eduarda Blanco-Rambo; Nadyne Rubin; Marcelo Bandeira-Guimarães; Caroline Muraro; Débora Marques; Andressa Fergutz; Greyse Dornelles; Caroline Pietta-Dias; Eduardo Lusa Cadore (Revista Brasileira de Atividade Física e Saúde)
The combination of strength and aerobic training (concurrent training - TG) has been a widely used intervention for improving health outcomes. Also, dance has been well described as a great aerobic activity and can be an interesting option to compose an alternative multicomponent training program. Therefore, the aim of the present protocol study is to describe the methods that will be used in a randomized controlled trial (RCT) design to identify and compare the impacts of traditional TG composed by strength and aerobic training and a multicomponent training consisting of strength training combined with dance classes (DG) on functional and cognitive capacity and quality of life of older people. The sample of RCT will consist of men and women aged between 60 and 75 years. Both interventions will occur twice a week for 12 weeks with progressive intensity and volume. Functional capacity will be assessed by gait, balance, sitting and standing and climbing tests. Strength will be assessed through one repetition maximum test (1RM) in knee extension exercise, and handgrip using a hand dynamometer. Muscle thickness will be assessed using quadriceps ultrasound. Muscle power will be assessed in the knee extension exercise at 30 and 70% of 1RM using an encoder. Aerobic capacity will be assessed using the 6-minute walk test. Quality of life and cognitive performance will be assessed by questionnaires. Comparisons between groups over time will be carried out using Generalized Estimating Equationswith a significance level of p<0.01. This protocol follows the recommendations of SPIRIT-2013.